Analysis of Factors Affecting Employee Engagement in Manufacturing Companies in Batam - Muhammad Donal Mon; Robin Robin; Ferdinand Nainggolan; Nova Sinambela (Universitas Padjadjaran, 2021)
This study aims to determine whether the variables of distributive justice, transformational leadership, training & development, and perceived organisational support affect employee engagement. This research was conducted using a survey method by distributing questionnaires to 500 respondents. The distribution of the questionnaires was carried out in two ways, namely, online via WhatsApp and manually, namely by visiting respondents. The sample of this research is employees who work in manufacturing companies in several industrial areas in Batam city. The industrial areas in question are the Batamindo industrial area, the Executive Batam Center industrial area, the Taiwan Kabil industrial area, and the Bintang industrial area in Tanjung Uncang. The technique used in this research is purposive sampling, which is a technique to determine the sample by using a special selection method to be used for processing properly. The results that have been collected from respondents, the data will be processed using SPSS software. This study indicates that transformational leadership has a positive and significant effect on employee engagement, training & development has a positive and significant effect on employee engagement, distributive justice has no effect on employee engagement, and perceptions of organisational support have no effect on employee engagement